Space boundary values and correct expansions of the Hermitian operators - Kuzhel, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
The concept of space of boundary values (SBV) is extended to the case of Hermitian, non-densely defined operators with distinct defect numbers. The properties of such SBV are investigated. The obtained results are applied to the investigation of regular (in particular, dissipative) extensions of Hermitian operators of the indicated form.